2011
DOI: 10.1177/0305735610386836
|View full text |Cite
|
Sign up to set email alerts
|

‘Rock music for myself and justice to the world!’: Musical identity, values, and music preferences

Abstract: The present study examined the relationship between music preferences, values, and musical identities in a sample of 606 Greek college students. Students indicated the importance of music in defining and evaluating themselves and their values on an abbreviated version of the Schwartz Value Survey (Schwartz, 1992). A typology of music preferences was revealed, with five factors: sophisticated and complex (e.g., jazz); native-Greek traditional (e.g., ‘rebetika’); sentimental and sensational (e.g., pop); establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
45
3
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 40 publications
3
45
3
4
Order By: Relevance
“…Basic personal values, on the other hand, operate in all domains of daily life. Basic personal values have been shown to influence attitudes and behavior in such domains as consumer choice (Pepper, Jackson, & Uzzell, 2009), music (Gardikoitis & Baltzis, 2012), sports (Lee, Hatzigeorgiadis, Whitehead, & Ntoumanis, 2008), and vocational interests (Sagiv, 2002), among many others. In short, core political values are a subset of basic personal values that help people make sense of the political world.…”
Section: Discussionmentioning
confidence: 99%
“…Basic personal values, on the other hand, operate in all domains of daily life. Basic personal values have been shown to influence attitudes and behavior in such domains as consumer choice (Pepper, Jackson, & Uzzell, 2009), music (Gardikoitis & Baltzis, 2012), sports (Lee, Hatzigeorgiadis, Whitehead, & Ntoumanis, 2008), and vocational interests (Sagiv, 2002), among many others. In short, core political values are a subset of basic personal values that help people make sense of the political world.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier research has demonstrated associations of the 10 values in the original theory with a wide variety of behaviors. Examples include helping behavior (Lönnqvist, Walkowitz, Wichardt, Lindeman, & Verkasalo, 2009), creative behavior (Kasof, Chen, Himsel, & Greenberger, 2007), interpersonal violence (Knafo, Daniel, & Khoury-Kassabri, 2008), risky sexual behavior (Goodwin et al, 2002), environmental behavior (Schultz & Zelezny, 1998), drug use (Tamayo, Nicaretta, Ribeiro, & de Barbosa, 1995), internet use (Hartman, Shim, Barber, & O'Brien, 2006), choice of medical specialty (Eliason & Schubot, 1995), consumer choices (Doran, 2009), and musical preferences (Gardikiotis & Blatzis, 2012). Neither these nor other studies provide evidence for the predictive validity of the refined values nor do they explicitly examine the effects on behavior of tradeoffs between opposing values.…”
mentioning
confidence: 99%
“…Individuals whose music tastes play a stronger role in their self‐identity might therefore exert more control over the music they listen to and show a strong preference or dislike toward certain genres. Based on the work of Gardikiotis and Baltzis (), we use the term musical identity to refer to the perceived importance of music in constructing one's self‐identity.…”
Section: Literature Reviewmentioning
confidence: 99%